Chronic disease and lifestyle factors associated with change in sleep duration among older adults in the Singapore Chinese Health Study. (28th September 2015) - Smagula, Stephen F.; Koh, Woon‐Puay; Wang, Renwei; Yuan, Jian‐Min
Summary: Identifying risk factors for future change in sleep duration can clarify whether, and if so how, sleep and morbidity are bidirectionally related. To date, only limited longitudinal evidence exists characterizing changes to sleep duration among older adults. This study aimed to identify factors associated with change in sleep duration in a large sample of older adults (≥ 60 years) residing in Singapore ( n  = 10 335). These adults were monitored as part of the Singapore Chinese Health Study, which collected information regarding daily sleep duration at baseline (assessed in 1993–1998) and at a follow‐up wave conducted over a mean of 12.7 years later (assessed in 2006–2010). Among adults sleeping 6–8 h at baseline ( n  = 8265), most participants (55.6%) remained 6–8 h sleepers at follow‐up, while 8.4% became short (< 6 h) and 36.0% became long (> 8 h) sleepers. A history of stroke, diabetes, cancer, hip fracture and greater age all independently increased the odds of having long sleep duration at follow‐up, while greater educational attainment and weekly physical activity were both associated with reduced odds of becoming a long sleeper. Other than greater baseline age, the only factor related to higher odds of becoming a short sleeper was concurrent stomach/duodenal ulcer at follow‐up. Long sleep duration among older adults may therefore reflect longstanding disease processes, whereas the aetiology of short sleep may predominately involve factors other than those examined. Future research is needed to distinguish if/when long sleep duration serves the disease recovery process, and when long sleep duration complicates disease and requires sleep medicine interventions.